Anxiety associated with COVID-19 and concerns about death: Impacts on psychological well-being - Silva, Washington Allysson Dantas (Pers Individ Dif, 2021)
Situations of public calamity, such as that caused by COVID-19 pandemic, strongly impact mental health, especially among people who feel most anxious about the imminence of death, as highlighted by the Terror Management Theory. In this research, we investigated how and under which conditions concerns about death itself and anxiety are related to psychological well-being. Specifically, we assessed the role of fear caused by the prominence of death (contextual and dispositional) in anxiety and well-being during the pandemic. Participants were 352 Brazilians, who answered a measurement of fear of death and read a news story about COVID-19. The manipulated news brought the idea of death to prominence (vs. non-prominence). After reading the news, the participants answered scales of anxiety and psychological well-being. The results showed that individual differences in fear of death related to well-being, and that this relationship was mediated by anxiety in face of COVID-19. Contrastingly, the manipulation of the salience of death in the news did not affect this relationship. These results contribute to the understanding of a psychological process related with fluctuations in individuals' well-being during the pandemic, offering insights for future studies that can promote better coping conditions during this period of world crisis.